Environmental, Social, and Governance and Financial Stability in OECD Banks - Mujib, Maliha (2025)
A Master of Science in Finance (MSF) by Maliha Mujib entitled, “Environmental, Social, and Governance and Financial Stability in OECD Banks”, submitted in December 2025. Thesis advisor is Dr. Donghyeok Jang. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).